2019
DOI: 10.1016/j.jmapro.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of creep age forming of AA7B04 stiffened plates: Experiment and FE modelling

Abstract: Creep age forming (CAF) of aluminium alloy 7B04 (AA7B04) stiffened plates has been experimentally and numerically investigated in this study. Creep-ageing experiments of AA7B04-T651 were conducted under different tensile stress levels at 140 °C for up to 20 h, and a set of unified constitutive equations was calibrated based on the experimental results of the evolutions of creep strain, yield strength and precipitate size, which was implemented into ABAQUS for CAF process modelling. CAF experiments and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…As the creep strains generated during CAF are very small, e.g. 0.25% after 20 h creep-ageing of AA7B04-T651 under 270 MPa at 140 °C [8], 0.2% used for engineering applications may ignore too many plastic strains when considering the small accumulated creep strains. Hence, 0.01% was used to divide the elastic and plastic regions of the material during loading in this study, and based on which, SRA tests were carried out under six initial stress/strain levels at each temperature, three in the elastic region and three in the plastic region, as listed in Table 2 Both SRA and tensile tests were executed on an Instron 5584 machine with an affiliated furnace which provides the high temperature environment for SRA tests.…”
Section: Stress Relaxation Ageing and Tensile Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the creep strains generated during CAF are very small, e.g. 0.25% after 20 h creep-ageing of AA7B04-T651 under 270 MPa at 140 °C [8], 0.2% used for engineering applications may ignore too many plastic strains when considering the small accumulated creep strains. Hence, 0.01% was used to divide the elastic and plastic regions of the material during loading in this study, and based on which, SRA tests were carried out under six initial stress/strain levels at each temperature, three in the elastic region and three in the plastic region, as listed in Table 2 Both SRA and tensile tests were executed on an Instron 5584 machine with an affiliated furnace which provides the high temperature environment for SRA tests.…”
Section: Stress Relaxation Ageing and Tensile Testsmentioning
confidence: 99%
“…Holman [5] has been reported that the conventional large/extra-large skins in the airplanes, such as wings, can be manufactured by CAF process in the elastic region, and thus, many studies focused on investigating [6] and modelling [7] the creep-ageing behaviour of aluminium alloys in the elastic region to guide potential CAF applications. However, Lyu et al [8] have reported that it is easy to reach plastic deformation region when the stiffened panels are loaded to the same shape of skins for CAF manufacture, and the current knowledge and models developed for creep-ageing in the elastic region may not be able to provide an accurate prediction of the springback of stiffened panels after CAF. Hence, a comprehensive understanding of the creep-ageing behaviour under different stress levels in both elastic and plastic regions becomes necessary for advanced industrial applications of CAF process.…”
Section: Introductionmentioning
confidence: 99%
“…Flat stiffened panels are often formed to desired shapes for particular applications by different forming technologies such as creep age forming, during which bending is one of the most common loading conditions. Buckling may occur in the stiffener area of the stiffened panels during bending due to the high concentrated stresses at the top of the stiffeners, which could lead to failure of stiffened panels in the forming process [13]. On the other hand, stiffener design can be optimised to avoid possible buckling problem.…”
Section: Nomenclaturementioning
confidence: 99%
“…The torsional moment is equal to the bending moment on the connecting edge of the stiffener ( ), which is a sinusoid function according to Eqs. (13) and (17). As indicated in Section 3.1, ′ cannot be obtained analytically for the flexible skin case, FE simulations have been used in this study to investigate the detailed non-rigid rotation behaviour of the flexible skin subjected to a torsional moment with a sinusoid function along the connecting edge.…”
Section: Boundary Conditions Of Buckling Modelmentioning
confidence: 99%
“…The developed material model is implemented into the commercial FE solver ABAQUS via the user-defined subroutine CREEP for process simulation. Both explicit and implicit methods have been used in previous studies on FE simulations of the SRAF process of aluminium alloys [7,22], and the explicit method has been found to be more straightforward and convenient to use, with satisfying results. Therefore, the explicit integration algorithms are used in this work, and all the material constants and initial values are defined in the subroutine.…”
Section: Implementation Of Materials Modelmentioning
confidence: 99%